PENGGUNAAN BUNGKIL INTI SAWIT YANG DIBERI HEMICELL DALAM RANSUM TERHADAP ENERGI METABOLISME RANSUM ITIK RAJA UMUR 7 MINGGU - Elman Halawa (Jurnal Peternakan Integratif, 2012)
Palm kernel cake as one of potential alternative feed stuff that contain good enough nutritions. Palm kernel cake has a high content of crude fiber, so, it needs to be treated to improve quality. Used of hemicell on palm kernel cake is expected to decrease crude fiber content of palm kernel cake, which can improve the quality of rations and improve nitrogen retention, energy metabolism and conversion energy nitrogen metabolism corrected from gross energy on Raja duck. Rations used were homemade. Research design used complete randomized design with five  treatments and four replications. R0 (without palm kernel cake which is mixed with hemicell), R1 (5% palm kernel cake which is mixed with hemicell), R2 (10% palm kernel cake which is mixed with hemicell), R3 (15% palm kernel cake which is mixed with hemicell), R4 (20 palm kernel cake which is mixed with hemicell). The observed of parameters are average digestible of crude fiber, retention nitrogen and metabolism energy on Raja duck. The results showed that the treatments give not significant differenc (P<0,05) of retention nitrogen, metabolisme energy and conversion energy nitrogen metabolisme corrected from gross energy on Raja duck feed. The use of palm kernel cake were given hemicell 2 cc/kg  can given to the level of 20% as the material ration raja duck 7 week age. Keywords: Palm kernel cake, Hemicell ®, Raja duck, Metabolisme Energy